Enhancing Transparency And Efficiency Through An Innovative Cash Receipt Accounting Information System At J&T Express Pringsewu Branch (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This research focuses on developing a prototype of a Logistics Accounting Information System to enhance transparency, efficiency, and accuracy in financial and delivery management. The study applies Object-Oriented Analysis and Design (OOAD) using UML modeling, including use case diagrams, class diagrams, sequence diagrams, and interface prototypes. Functional requirements such as transaction recording, financial reporting, and user management were identified, along with non-functional requirements including security, usability, reliability, and scalability. The resulting prototype integrates logistics and accounting processes into a unified platform, supporting roles such as cashier, administrator, and branch head. Key features include transaction validation, delivery tracking, and automated report generation, which strengthen decision-making and operational control. This system addresses the limitations of manual processes and provides a reliable foundation for future implementation, offering significant potential to improve the performance and accountability of logistics accounting operations.
Keywords: Accounting Information System; Cash Receipt; J&T Express; System Design